Electronic spectroscopy of isolated DNA polyanions. (29th April 2019) - Daly, Steven; Porrini, Massimiliano; Rosu, Frédéric; Gabelica, Valérie
Abstract : We address whether action spectroscopy could be used to investigate structural changes in gas-phase biomolecule ( e.g. nucleic acid) ions, owing to changes in the environments of their chromophores, while taking advantage of the additional spectrometric separation of complex mixtures. Abstract : In solution, UV-vis spectroscopy is often used to investigate structural changes in biomolecules ( e.g., nucleic acids), owing to changes in the environment of their chromophores ( e.g., the nucleobases). Here we address whether action spectroscopy could achieve the same for gas-phase ions, while taking advantage of the additional spectrometric separation of complex mixtures. We systematically studied the action spectroscopy of homo-base 6-mer DNA strands (dG6, dA6, dC6, dT6 ) and discuss the results in light of gas-phase structures validated by ion mobility spectrometry and infrared ion spectroscopy, of electron binding energies measured by photoelectron spectroscopy, and of calculated electronic photo-absorption spectra. When UV photons interact with oligonucleotide polyanions, two main actions can take place: (1) fragmentation and (2) electron detachment. The action spectra reconstructed from fragmentation follow the absorption spectra well, and result from multiple cycles of photon absorption and internal conversion. In contrast, the action spectra reconstructed from the electron photodetachment (ePD) efficiency reveal interesting phenomena. First, ePD depends on the charge state because it depends on electron binding energies. We illustrate with the G-quadruplex [dTG4 T]4 that the ePD action spectrum shifts with the charge state, pointing to possible caveats when comparing the spectra of systems having different charge densities to deduce structural parameters. Second, ePD is particularly efficient for purines but not pyrimidines. ePD thus reflects not only absorption, but also particular relaxation pathways of the electronic excited states. As these pathways lead to photo-oxidation, their investigation in model gas-phase systems may prove useful to elucidating mechanisms of photo-oxidative damage, which are linked to mutations and cancers.